Percutaneous atrial septal defect closure in limited-resource setting: a decade-long experience from Ethiopia - Nasir, Mohammed; Dejene, Kefelegn; Bedru, Mohammed; Markos, Sura (Frontiers in Cardiovascular Medicine, 2025)
IntroductionSecundum Atrial septal defect (ASD) is the most common type of ASD. When it is large and hemodynamically significant, it can cause symptoms such as dyspnea, exercise intolerance, and palpitations. Following diagnosis confirmation, an ASD with hemodynamic significance should be closed electively. Percutaneous closure (PC) is an effective treatment option for ostium secundum ASD with adequate rims, despite the potential for several complications. This is the first study in Ethiopia and sub-Saharan Africa to report on percutaneous closure of secundum atrial septal defects (ASD) in children, adolescents, and adults. The study assessed the clinical characteristics, immediate and in-hospital outcomes, and complication rates following PC of secundum ASD.Methodologyhis follow-up study, conducted between October 2023 and January 2024, involved 99 patients who underwent percutaneous closure (PC) of ASD at the Cardiac Center of Ethiopia between January 2013 and January 2023. The patients were divided into two groups based on age: Group 1 included children and adolescents (≤18 years of age; n = 42), while Group 2 consisted of adults (>18 years of age; n = 57), at the time of device percutaneous closure. The median and interquartile range was used to describe continuous variables. The absolute frequency and percentages were used to describe the categorical variables. The data were shown using tables and graphs. Baseline characteristics of patients of ≤18 years vs. >18 years were compared using the Mann–Whitney U-test for continuous variables and the Chi-square or Fisher exact test for categorical data.ResultsThere was a female predominance with female to male ratio of 1.3. Compared to Group 1 (children and adolescents of age ≤ 18 years), more patients in Group 2(adults of age > 18 years) experienced symptoms (p-value < 0.001). The most common symptoms in adults were easy fatigability and dyspnea (63.2% of adult patients), while the most common symptom in children was recurrent respiratory tract infections (23.8%). Patients in Group 2 had greater pulmonary artery systolic pressure than those in Group 1 (p-value < 0.001). Overall, 88.9% of patients attained immediate success; there was no statistically significant difference between the two groups in immediate success rate (p = 0.52; Group 1 85.7% vs. Group 2 91.2%). Overall, patients' median length of hospital stay was 2 days (IQR, 2–2.5 days). There was no statistically significant difference between the two groups' median hospital stays [Group 1: 2 (IQR, 2–2.5) and Group 2: 2.5 (IQR 2–2.5); P-value = 0.111]. 23.2% of patients experienced complications, with no significant difference between the two groups (Group 1 28.6% and Group 2 19.3%, p = 0.28). The most common complications for patients in Groups 1 and 2 were atrioventricular (AV) valve encroachment (4.8) and paroxysmal supraventricular tachycardia (SVT) (5.3%), respectively. The major complication rates in the two groups did not show a statistically significant difference. Group 1 had a rate of 4.8%, whereas Group 2 had a rate of 0% (p-value = 0.18). The length of stays significantly increased in both groups in the presence of complications (p-value < 0.001).ConclusionThis study emphasized that Percutaneous Closure of ASD can be successfully performed in resource-limited settings with a high immediate success rate and minimal complications such as AV valve encroachment and paroxysmal SVT. Given that complications impact length of hospital stays, preventing them is crucial.